Theorizing Autobiography and Materialist Feminist Pedagogy - Martindale, Kathleen (Canadian Journal of Education/Revue canadienne de l'éducation, 1992)
This article offers a materialist feminist critique of commonly held, although naturalizing assumptions, about the appropriateness of “nurturant” pedagogy in feminist university classrooms. Using, yet interrupting, the theoretical autobio- graphical accounts of British feminist educators Valerie Walkerdine and Carolyn Steedman and American literary critic bell hooks, I interpolate passages from my own educational autobiography in my own critique, thus illustrating how what I call a “deconstructivist materialist feminist” pedagogy works in classroom situa- tions. Cet article fait appel au féminisme matérialiste pour critiquer des hypothèses courantes, quoique naturalistes, sur la pertinence d’une pédagogie “nurturante” dans les salles de cours féministes des universités. Utilisant tout en les question- nant les comptes rendus autobiographiques théoriques des éducatrices féministes britanniques Valerie Walkerdine et Carolyn Steedman et de la critique littéraire américaine bell hooks, l’auteure interpole des passages de sa propre autobiogra- phie d’éducatrice dans sa critique, illustrant ainsi comment la pédagogie “fémini- ste matérialiste déconstructiviste” fonctionne dans les salles de cours.